Magnetite supported hematin as a biomimetic of horseradish peroxidase phenol removal by polymerization - Ambrosio, Karina (2004)
Phenol removal using HRP and hematin as biomimetic of HRP is presented at selected conditions at room temperature. The best results are obtained with treatment in two steps, with double addition of HRP or hematin and a final treatment with activated carbon. This two-step treatment achieved 90 % minimal conversion of initial phenol, at conditions commonly found in wastewaters (from 400 up to 1500 ppm phenol). Other additives such as chitosan, cellulose or polyethylenglycol (PEG) gave no satisfactory results. Hematin and magnetite-supported hematin showed comparable activities in phenol removal from aqueous solution. The supported hematin is an interesting alternative to HRP for practical application of biomimetic catalyst to phenol removal.